Fungal Infections Complicating Lung Transplantation - Clark, Nina M.; Weigt, S. Samuel; Fishbein, Michael C.; Kubak, Bernard; Belperio, John A.; Lynch, Joseph P., III (Seminars in Respiratory and Critical Care Medicine, 2018)
Lung transplantation is an increasingly utilized modality for treating advanced lung disease. However, lung transplant recipients (LTRs) experience high rates of infection-related mortality and, compared with other solid organ transplant recipients, are at increased risk of infectious complications given the intensity of immunosuppression employed, the presence of airway abnormalities after surgery and exposure of the allograft to the environment. Fungal infections, particularly mold infections, are problematic after transplantation as they are often associated with limited treatment options and poor outcomes. We describe the non-Candida fungal infections occurring in LTRs, including their epidemiology, clinical features, and treatment.
Keywords: invasive fungal infections; mold; organ transplant; lung transplant; aspergillosis; mucormycosis; fusariosis; scedosporiosis; triazoles